Head‐to‐head comparison of ranibizumab PRN versus single‐dose dexamethasone for branch retinal vein occlusion (COMRADE‐B). Issue 1 (2nd March 2017) - Hattenbach, Lars‐Olof; Feltgen, Nicolas; Bertelmann, Thomas; Schmitz‐Valckenberg, Steffen; Berk, Hüsnü; Eter, Nicole; Lang, Gabriele E.; Rehak, Matus; Taylor, Simon R.; Wolf, Armin; Weiss, Claudia; Paulus, Eva‐Maria; et al.
Abstract: Purpose: To compare the efficacy and safety of ranibizumab 0.5 mg versus dexamethasone 0.7 mg according to their European labels in macular oedema secondary to branch retinal vein occlusion (BRVO) in a 6‐month, phase IIIb, randomized trial. Methods: Patients received either monthly ranibizumab for 3 months followed by Pro re nata (PRN) treatment ( n  = 126) or a sustained‐release dexamethasone implant followed by PRN sham injections ( n  = 118). Main outcomes were mean average change in best‐corrected visual acuity (BCVA) from baseline to month 1 through month 6, mean changes in BCVA and foveal centre point thickness (FCPT), and adverse events (AEs). Results: There was no difference in BCVA gains between the treatments prior to month 3. Best‐corrected visual acuity (BCVA) gain with dexamethasone declined thereafter. From month 3 to month 6, mean BCVA change from baseline was significantly higher with ranibizumab than with dexamethasone [raw means (standard deviation):+16.2 (±11) letters versus +9.3 (±10.1) letters]. At month 6, the difference in BCVA gains from baseline was +17.3 letters in the ranibizumab versus +9.2 letters in the dexamethasone group. Patients in the ranibizumab group received a mean of 2.94 loading injections and 1.74 PRN retreatment injections, while those in the dexamethasone group received a single loading injection. Elevated intraocular pressure (IOP) and AEs were more frequent with dexamethasone than ranibizumab treatment. Conclusion: Ranibizumab PRN resulted in greater visual acuity (VA) gains in macular oedema following BRVO compared with single‐dose dexamethasone over a 6‐month study period, observed from month 3, when administered according to their European label. In clinical practice, retreatment with dexamethasone may be required prior to this point.